Pengaruh Komunikasi Interpersonal, Budaya Sekolah dan Peran Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di Sekolah Menengah Kejuruan Negeri - Andika Saputra; Abdullah Umar; Ida Hannum; Ahmad Zulfan Hasibuan; Irsan Efendi Nasution; Safrida; Neni Sri Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The formulation of problem in this research is there is influence interpersonal communication on teachers performance. There is influence school culture on teachers performance. There is head school leadership roel on teachers performance. There is influence of interpersonal communication, school culture and head school leadership roel on teachers performance. The purpose of this research is for know influence and analize of interpersonal communication on teachers performance. For know influence and analize school culture on teachers performance. For know influence and analize head school leadership roel on teachers performance. For know influence and analize interpersonal communication, school culture and head school leadership roel on teachers performance. The sample in this research is 31 teachers, with data analysis technique used is multiple linear regression analysis. The research result interpersonal communication influence positive and significant on teachers performance. School culture influence positive and significant to teachers performance. Head school leadership roel influence positive and significant to teachers performance. Interpersonal communication, school culture and head school leadership roel influence positive and significant to teachers performance